2017
DOI: 10.1142/s0192415x17500768
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Autophagy in Ischemic Heart Diseases and the Modulatory Effects of Chinese Herbal Medicine

Abstract: Autophagy is an evolutionarily conserved degradation process which eliminates dysfunctional proteins and cytoplasmic components to maintain homeostasis for cell survival. Increasing evidence has demonstrated the modulatory role of autophagy in ischemic heart diseases (IHDs). Traditionally, this process has been recognized as having protective functions, such as inhibiting atherosclerosis progression and reducing cell death during the ischemic phase. However, recent studies have suggested its dual roles in myoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…In addition to cytoprotective effects, autophagy exerts a death stimulation function, known as autophagic cell death, depending on the specific conditions [4]. In the meantime, autophagy offers a therapeutic opportunity to patients with diverse diseases, such as rheumatic diseases, ischemic heart diseases, central nervous system (CNS) diseases and tumors by modulating apoptosis, inflammation, immune responses, and other intracellular processes [58]. Nevertheless, the defective specificity of autophagy activators or inhibitors limits their clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to cytoprotective effects, autophagy exerts a death stimulation function, known as autophagic cell death, depending on the specific conditions [4]. In the meantime, autophagy offers a therapeutic opportunity to patients with diverse diseases, such as rheumatic diseases, ischemic heart diseases, central nervous system (CNS) diseases and tumors by modulating apoptosis, inflammation, immune responses, and other intracellular processes [58]. Nevertheless, the defective specificity of autophagy activators or inhibitors limits their clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, accumulated studies reported that herbals could protect against ischemic cardiomyopathy by regulating autophagy [29]. Gingko biloba leaf extract (GBE), which contains terpenoids, flavonoids, alkylphenols, polyprenols, and organic acids, has long been used for the treatment of cardiovascular disease [30].…”
Section: Introductionmentioning
confidence: 99%
“…These data indicate that autophagy is involved in the inflammation of GO orbitals. 17 Autophagy in ischemic heart diseases inhibiting atherosclerosis progression and reducing cell death during the ischemic phase. Crucial role of adenosine monophosphateactivated protein kinase (AMPK) induced autophagy in maintaining cellular homeostasis under conditions of energy deprivation.…”
Section: Discussionmentioning
confidence: 99%